Ion irradiation introduced high-density core-shell structured nanoprecipitates in FeCrNi - Yizhou Qian; Xiaolei Ma; Kangkang Wen; Siyu Chen; Yiheng Chen; Yugang Wang; Tongde Shen; Gang Sha; Chenxu Wang (Journal of Materials Research and Technology)
This study explores the novel synthesis of high-density core-shell structured nanoprecipitates (NPs) within FeCrNi alloys via ion irradiation, aiming to enhance mechanical properties through NPs. We have successfully prepared NPs in FeCrNi with an average diameter of ∼15.2 nm and a number density of ∼2.03 × 1022 m−3 by employing ion irradiation. Transmission Electron Microscopy (TEM) and Atom Probe Tomography (APT) results show the unique core-shell structure of these NPs, consisting of Cr-rich M23C6 carbides cores and Ni-rich shells. The ion irradiation process facilitated the controlled formation of these nanostructures by inducing localized vacancies, which allowed the nucleation and growth of NPs uniformly distributed within the alloy matrix. This synthesis method overcomes traditional limitations posed by thermodynamic constraints and grain boundary (GB) agglomeration, providing a potential pathway for the precise tailoring of microstructures. The combination of APT and TEM analysis offers detailed insight into the structural evolution of the core-shell NPs. These findings represent ion irradiation as an effective technique for fabricating novel nanostructures and hold potential for further improvements in mechanical properties, particularly in the strength, of FeCrNi alloys. Future studies will focus on evaluating the impact of varying irradiation parameters and carbon content on the structural and mechanical characteristics of these alloys.